How to profile an innovation bundle - Minh, Thai Thi; Ofosu, Abena; Gbodji, Kekeli (International Water Management Institute, 2023)
Profiling an innovation bundle describes the bundle and bundling process, assesses its scalability, and identifies possible pathways to adapt and scale existing bundles to different areas.